The role of connections in academic promotions - Natalia Zinovyeva; Manuel F. Bagues (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the role of connections in academic promotions. We exploit evidence from centralized evaluations in Spain, where evaluators are randomly assigned to promotion committees. We find that prior connections between candidates and evaluators have a dramatic impact on candidates' success. For instance, the presence of a co-author or an advisor in the committee is equivalent to a standard deviation increase in candidates' research output. The effect of a weaker link, such as a member of candidate's doctoral thesis committee, is one fourth as large. The source of the premium enjoyed by connected candidates depends on the nature of their relationship with committee members. In the case of weak links, informational gains tend to dominate evaluation biases. Candidates promoted by a weak link turn out to be more productive in the future relative to other promoted candidates. However, consistently with the potential existence of favoritism, candidates promoted by a strong connection exhibit a significantly worse research record both before and after the evaluation.
Keywords: J44; M51; 330; academic promotions; connections; evaluation bias; information asymmetries